The Virtual Health Clinic in the training of the dentistry resident - Ayvanka León Quintela; Nancy María Rodríguez Beltrán; Humberto Manuel Rodríguez Rey (Centro Provincial de Información de Ciencias Médicas, 2024)
Introduction: Nowadays, in the Health National System there is a growing interest for the development of virtual contexts with teaching ends, such as the Health Virtual Clinic.  Objective: To design a system of actions for using Virtual Health Clinic in the training of the dentistry resident. Methods: An educational investigation was carried out, in Medical Education environment, from December 2021 to April, 2022, in the Stomatology Faculty of the University of Medical Sciences in Santiago de Cuba.  Results: In the exploratory phase the following problems were identified: insufficient training activities directed to dentistry residents and difficulties to satisfy the necessities of information as for search, restoration and evaluation in Health Virtual Clinic. On the other hand, orthodontia specialty has obtained technical scientific results that back its high level and there is a will of implementing the proposal as support to the training process of these residents to transform inadequacies.  Conclusions: The designed system of actions is characterized to be open, flexible, innovative and contextualized, which favors the appropriate use of Health Virtual Clinic in the training process of dentists residents.